2019
DOI: 10.14393/bj-v35n2a20198-42109
|View full text |Cite
|
Sign up to set email alerts
|

β -Glucan from Saccharomyces cereviseae in skim yogurt production

Abstract: The demand for functional foods has increased in recent years, following a market trend in which the consumer values foods associated with health improvements. Skim milk yogurts were produced with yeast β-glucan (YBG, 0.5 and 1.0 %) isolated from Saccharomyces cerevisiae and compared with full fat (FFY) and skim milk (SMY) yogurt as controls. The samples were analyzed for physical, chemical, color, syneresis, culture starter count, textural, microstructure and sensory attributes. Yeast β-glucan was not able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A study of the addition in nonfat yogurts of β-glucans up to a level of 2% concluded that at a concentration of 1.5% β-glucan, an important improvement in consistency, viscosity index and rheological properties during 28 days of storage was observed [ 144 ]. Also, Dos Santos et al in 2019 by using β-glucan extracted through the alkaline method in concentrations up to 1% ( w / v ) noted major textural changes skimmed yogurt [ 176 ].…”
Section: Food Applicationsmentioning
confidence: 99%
“…A study of the addition in nonfat yogurts of β-glucans up to a level of 2% concluded that at a concentration of 1.5% β-glucan, an important improvement in consistency, viscosity index and rheological properties during 28 days of storage was observed [ 144 ]. Also, Dos Santos et al in 2019 by using β-glucan extracted through the alkaline method in concentrations up to 1% ( w / v ) noted major textural changes skimmed yogurt [ 176 ].…”
Section: Food Applicationsmentioning
confidence: 99%